Terrorist Warfare: Formidable Challenges - Motley, James B. (Tufts Archival Research Center, 2005)
Volume 9, Issue 2. Summer In this article, Dr. Motley assesses terrorism as a form of warfare. He identifies the place which terrorism occupies on a spectrum of military conflict differentiated by risk, probability of occurrence, and level of intensity. Dr. Motley draws upon this model to outline a corresponding defensive role for U.S. armed forces - a role for which those forces must adapt. The probable increasing use of terrorist tactics to pursue military objectives in opposition to U.S. interests requires that the U.S. develop the necessary tactical skill and flexibility to meet this threat, he concludes.